The patellofemoral joint: from dysplasia to dislocation. Issue 5 (11th May 2017) - Zaffagnini, Stefano; Grassi, Alberto; Zocco, Gianluca; Rosa, Michele Attilo; Signorelli, Cecilia; Muccioli, Giulio Maria Marcheggiani
Abstract : Patellofemoral dysplasia is a major predisposing factor for instability of the patellofemoral joint. However, there is no consensus as to whether patellofemoral dysplasia is genetic in origin, caused by imbalanced forces producing maltracking and remodelling of the trochlea during infancy and growth, or due to other unknown and unexplored factors. The biomechanical effects of patellofemoral dysplasia on patellar stability and on surgical procedures have not been fully investigated. Also, different anatomical and demographic risk factors have been suggested, in an attempt to identify the recurrent dislocators. Therefore, a comprehensive evaluation of all the radiographic, MRI and CT parameters can help the clinician to assess patients with primary and recurrent patellar dislocation and guide management. Patellofemoral dysplasia still represents an extremely challenging condition to manage. Its controversial aetiology and its complex biomechanical behaviour continue to pose more questions than answers to the research community, which reflects the lack of universally accepted guidelines for the correct treatment. However, due to the complexity of this condition, an extremely personalised approach should be reserved for each patient, in considering and addressing the anatomical abnormalities responsible for the symptoms. Cite this article: EFORT Open Rev 2017;2. DOI: 10.1302/2058-5241.2.160081. Originally published online at www.efortopenreviews.org